2022
DOI: 10.1111/jopy.12789
|View full text |Cite
|
Sign up to set email alerts
|

Personality maturation through sense of mastery? Longitudinal evidence from two education‐to‐work transition studies

Abstract: has been submitted for publication and has not yet been peer reviewed. AcknowledgementsThis research has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 846839, awarded to Anne Reitz. There are no conflicts of interest to disclose.The preregistration of hypotheses and the analysis plan, code, and data are available on the OSF (https://osf.io/ksugw/). The research materials can also be found on the OSF (Study 1: https:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Therefore, mastery experiences before the transition may not explain why some individuals increase whereas others decrease in state self-esteem during the university-to-work transition. Taken together, our findings across months support the theoretical notion that change during major life transitions may be triggered by mastery experiences during the transition (Reitz et al, 2022; Roberts & Nickel, 2021) such as mastery of the age-graded developmental tasks (Havighurst, 1976) and mastery of the new social role that young adults invest in (Roberts & Nickel, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, mastery experiences before the transition may not explain why some individuals increase whereas others decrease in state self-esteem during the university-to-work transition. Taken together, our findings across months support the theoretical notion that change during major life transitions may be triggered by mastery experiences during the transition (Reitz et al, 2022; Roberts & Nickel, 2021) such as mastery of the age-graded developmental tasks (Havighurst, 1976) and mastery of the new social role that young adults invest in (Roberts & Nickel, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…As self-esteem fluctuates in response to success and failure (Crocker et al, 2002), major life transitions may elicit normative and heterogeneous trait self-esteem change depending on the mastery experiences during transitions (Reitz, 2022). There is evidence for average trait self-esteem change during relational (e.g., Lehnart et al, 2010; Luciano & Orth, 2017), educational (e.g., Chung et al, 2014; Hutteman et al, 2015), and work transitions (e.g., Reitz et al, 2022; for a review, see Reitz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has conducted such studies (GradLife: job entry; STRIDE: educational transition; NiMO: motherhood). For job entry, we found dynamic links between daily mastery and personality states (Reitz et al, 2022a) and between pride and self-esteem across days and co-development across the transition (Diwan et al, 2023).…”
Section: Methodologies Suited To Capture the Individual Experience Of...mentioning
confidence: 99%
“…Using multiple data sets, different SES indicators, and testing moderation effects with age and childhood SES was crucial in understanding how educational and economic factors are linked to individual differences and potential trait developments over time. Reitz et al (2023; this issue) examined Big Five personality traits/states and mastery changes in the education-towork transition in two samples. Although there was not strong evidence for the maturational principle in these studies, they found that people with more work-related mastery tended to increase in conscientiousness over time.…”
Section: Overview Of Papersmentioning
confidence: 99%
“…Reitz et al (2023; this issue) examined Big Five personality traits/states and mastery changes in the education‐to‐work transition in two samples. Although there was not strong evidence for the maturational principle in these studies, they found that people with more work‐related mastery tended to increase in conscientiousness over time.…”
Section: Overview Of Papersmentioning
confidence: 99%